Comparative efficacy of LaSota, B1 and Mukteswar Strain vaccines for Newcastle Disease Virus (NDV) in layer chickens (Asian Journal of Medical and Biological Research, 2021)
The control of Newcastle Disease (ND) relies on the use of safe and effective vaccines. Live vaccines which are prepared with lentogenic strains of Newcastle Disease Virus (NDV) are now more frequently used in broilers and layers than vaccines prepared from chemically inactivated strains of NDV mixed with adjuvant. This is because live freeze-dried vaccines can be produced on a large scale at a relative low cost. The vaccines are easy to administer on large scale, and rapidly stimulate cell-mediated and mucosal surface immunity. The present study was designed to compare the efficacy of LaSota, B1 and Mukteswar Strain vaccines for NDV in layer chickens. Findings of our present study indicated that production of HI-antibody titre was higher in birds of group A (512) vaccinated with ND LaSota, compared to those of group B (256) vaccinated with RDV (Mukteswar strain); group C (128) vaccinated with ND B1 (B1 strain) Hitchner at six weeks after vaccination. Thus, the ND LaSota vaccine was found to be superior to some extent than ND B1 Hitchner. However, as regards vaccination of chicks against NDV in earlier days, the use of lentogenic strains are recommended although it should be kept in mind that vaccination with LaSota strains would cause greater problems in young susceptible birds than Hitchner B1 strain and even though LaSota induces stronger immune responseAsian J. Med. Biol. Res. 2021, 7 (4), 332-338